OBSTACLES TEACHERS FACE IN INTEGRATING ICT INTO ELT IN SENIOR HIGH SCHOOLS IN PALEMBANG - Dedi - Kurniawan (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2014)
ICT proves to be beneficial to ELT. Thus, the integration is important but some obstacles are faced by teachers in the process. This is a descriptive study focusing on identifying obstacles in integrating ICT into ELT in teachers’ point of view. The subjects of this study, who completed a likert-like scale questionnaire investigating the obstacles, are fifty teachers from ten senior high schools in Palembang. The questionnaire investigates two levels of obstacles: (1) teacher-level obstacles and (2) school-level obstacles. The findings show that school-level obstacles, such as lack of professional development and training, lack of technical support, lack of incentives, lack of funding and lack of time, are more dominant factors as compared to teacher-level obstacles, such as lack of teacher competence and confidence, resistance to change and negative attitude. Some suggestions are offered based on the findings of this study.